Colossal magnetoresistance of La0.67Ca0.33Mn1-xAx)3 [A=V, Dy and Zr] perovskite - Koh, Song Foo (2001)
The colossal magnetoresistive of Lao.67Cao.33Mnl-x V x03 (LCMVO), to x=O.30, ceramics have been studied. X-ray diffraction (XRD) patterns show single-phase perovskite structure with the presence of some minor impurities for all the samples. The systems exhibit tetragonal and orthorhombic distorted perovskite structures, which resulted from the Jahn Teller distortion. Paramagnetic - Ferromagnetic phase transitions were observed in the X'-temperature curves for all the samples. The Curie temperature, Tc shifts to lower temperature as vanadium, dysprosium and zirconium doping increases respectively, which indicate the loss of ferromagnetic order. Zirconium doping is observed to decrease the Te more than the effect of other dopants. For LCMVO system, samples with x=0.0l, 0.02, 0.03 and 0.30 show an enhancement of volume susceptibility as the temperature increases from 110 K- 140 K, 120 K- 142 K, 123 K-140 K and 77 K-94 K respectively. These enhancements are due to the formation of magnetic clusters m the samples. For LCMDO system, all the samples show the typical ferromagnetic-paramagnetic transition and no spin glass behaviour was detected. However, in LCMZO system, the samples with x>0.05 show ferromagnetic onset followed by a cusp when cooling from room temperature. The anomalies were due to the formation of spin glass in the sample. The transport properties show the transition of semiconducting to metallic conductivity at T p. The existence of T p and T c was found correlated.